EFISIENSI PENGAWASAN INTERNAL TERHADAP MAHKAMAH KONSTITUSI OLEH MAJELIS KEHORMATAN MAHKAMAH KONSTITUSI - Rizal, Ahmad; Patra, Rommy; Suasono, Edy (Tanjungpura Legal Review, 2024)
AbstractBased on Law Number 7 of 2020 concerning the Third Amendment to Law Number 24 of 2003 concerning the Constitutional Court, the Constitutional Court is obliged to establish a supervisory institution, namely the Constitutional Court Honorary Council (Majelis Kehormatan Mahkamah Konstitusi/MKMK). This paper aims to analyze the efficiency of the MKMK as an internal supervisory institution for the Constitutional Court. The method used is a normative legal research method with descriptive analytical-case study research characteristics. The results of the analysis showed that MKMK was inefficient. There are two things that cause the MKMK to be inefficient, which are the spirit of defending fellow corps (espritde corps) which results in the passing of the law being disproportionate to the deeds and the MKMK as a supervisory institution in fact does not have effectiveness is due to its ad hoc nature. MKMK as a supervisory institution for constitutional judges would be better off being an independent institution so that it is free from the influence of the Constitutional Court itself. The MKMK working mechanism is still tied to the Constitutional Court, such as the formation of the MKMK, the element of Constitutional Court judges in the MKMK also causes the MKMK to appear to be taking a long time in carrying out its duties as a supervisory institution.  AbstrakBerdasarkan Undang-Undang Nomor 7 Tahun 2020 tentang Perubahan Ketiga Atas UndangUndang Nomor 24 Tahun 2003 tentang Mahkamah Konstitusi, Mahkamah Konstitusi berkewajiban untuk membentuk lembaga pengawas yaitu Majelis Kehormatan Mahkamah Konstitusi (MKMK). Tulisan ini bertujuan untuk menganalisis efisiensi MKMK sebagai lembaga pengawas internal Mahkamah Konstitusi. Metode yang digunakan adalah metode penelitian hukum normative dengan sifat penelitian deskriptif analitis. Hasil analisis didapatkan bahwa MKMK tidak efisien. Terdapat dua hal yang menyebabkan MKMK tidak efisien, yaitu adalah semangat membela sesama korps (espritde corps) yang mengakibatkan penjatuhan hukum tidak seimbang dengan perbuatan dan MKMK sebagai lembaga pengawas nyatanya tidak memiliki kefektivitasan disebabkan sifatnya selama ini ad hoc. MKMK sebagai lembaga  pengawas hakim konstitusi ada baiknya menjadi lembaga yang independen sehingga bebas dari pengaruh MK itu sendiri. Mekanisme kerja MKMK yang masih terikat pada MK seperti pembentukan MKMK, unsur hakim MK dalam MKMK juga menyebabkan MKMK terkesan lama dalam menjalankan tugasnya sebagai lembaga pengawas.